2020
DOI: 10.1186/s40001-020-00416-3
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of miR-210 is involved in the development of diabetic retinopathy and serves a regulatory role in retinal vascular endothelial cell proliferation

Abstract: Background: Diabetic retinopathy is a common complication of diabetes mellitus (DM). The purpose of this study was to investigate the expression and clinical significance of miR-210 in DR patients and explore the regulatory effect of miR-210 on vascular endothelial cell function under high-glucose condition. Methods: Quantitative real-time PCR was used to estimate miR-210 expression. A receiver operating characteristics curve (ROC) was plotted to evaluate the diagnostic value of miR-210. Human umbilical vein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
3
18
0
1
Order By: Relevance
“…Conversely, miR-495-3p was reportedly lower in patients with diabetic retinopathy [ 36 ]. miR-210 is also associated with diabetes mellitus and diabetic retinopathy, reportedly by mediating functional responses in endothelial cell function [ 37 ]. In a study of 150 type 2 diabetic patients, Yin et al found that serum miR-210 was increased in patients with diabetic retinopathy and was positively correlated with HbA1c, HOMA-IR, and fasting plasma glucose [ 37 ].…”
Section: Extracellular Mirnas In Type 2 Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, miR-495-3p was reportedly lower in patients with diabetic retinopathy [ 36 ]. miR-210 is also associated with diabetes mellitus and diabetic retinopathy, reportedly by mediating functional responses in endothelial cell function [ 37 ]. In a study of 150 type 2 diabetic patients, Yin et al found that serum miR-210 was increased in patients with diabetic retinopathy and was positively correlated with HbA1c, HOMA-IR, and fasting plasma glucose [ 37 ].…”
Section: Extracellular Mirnas In Type 2 Diabetesmentioning
confidence: 99%
“…miR-210 is also associated with diabetes mellitus and diabetic retinopathy, reportedly by mediating functional responses in endothelial cell function [ 37 ]. In a study of 150 type 2 diabetic patients, Yin et al found that serum miR-210 was increased in patients with diabetic retinopathy and was positively correlated with HbA1c, HOMA-IR, and fasting plasma glucose [ 37 ]. They also report that miR-210 could differentiate patients with diabetic retinopathy from the healthy controls, highlighting the diagnostic potential of this miR [ 37 ].…”
Section: Extracellular Mirnas In Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, proliferative DR (PDR) patients had higher levels than non-proliferative DR (NPDR) patients. The differential upregulation suggests that increased serum miR-210 could be used to identify patients with higher risk for PDR from NPDR patients (39). Two miRNAs mostly associated with the risk of DR in patients with T1DM are miR-27b and miR-320a (40).…”
Section: Circulatory Mirnas Potential As Early Diagnostic Tools For Drmentioning
confidence: 99%
“…Moreover, the expression of miR-210 was upregulated in the SAT of obese individuals with normal glucose tolerance, compared to those diagnosed with type 2 diabetes mellitus (T2DM), suggesting its protective role in the development of obesity-related adipose tissue dysfunction [ 34 ]. However, in patients with T2DM, serum miR-210 concentration may serve as a diagnostic biomarker of diabetic retinopathy patients and may have the ability to predict disease development and severity [ 35 ].…”
Section: Role Of Micrornas In Adipogenesismentioning
confidence: 99%